DIGITAL LEADERSHIP DALAM PENGELOLAAN MGMP DAN KAITANNYA DENGAN EFEKTIVITAS SERTA KESIAPAN DIGITAL GURU - Uchtiana Uchtiana; Elvirawati Elvirawati; Anidar Anidar; Marnita Marnita (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
ABSTRACT This study aimed to analyze digital leadership in the management of Subject Teacher Working Groups (MGMP), the effectiveness of activity implementation, and the digital readiness of its members. The study employed a descriptive quantitative approach with a survey design involving 50 elementary school MGMP members in Bireuen Regency, Aceh. Data were collected using a Likert-scale questionnaire covering digital leadership, management effectiveness, and members’ digital readiness, and were analyzed descriptively using mean scores. The findings revealed that digital leadership was categorized as high with a mean score of 3.80, while the effectiveness of MGMP management was categorized as very high with a mean score of 4.00. Meanwhile, members’ digital readiness was categorized as moderate with a mean score of 3.60, particularly regarding perceptions of the benefits of technology in improving the quality of activities. The findings indicate that the use of technology has supported organizational management and communication; however, it has not been fully accompanied by the strengthening of digital vision and the equal improvement of members’ digital readiness. Therefore, strengthening the organizational digital vision, enhancing technology-based leadership competencies, and optimizing digital culture are necessary to support sustainable teacher professional development in the digital era. ABSTRAK Penelitian ini bertujuan menganalisis kepemimpinan digital dalam pengelolaan Musyawarah Guru Mata Pelajaran (MGMP), efektivitas pelaksanaan kegiatan, serta kesiapan digital anggotanya. Penelitian menggunakan pendekatan kuantitatif deskriptif dengan desain survei terhadap 50 anggota MGMP SD di Kabupaten Bireuen, Aceh. Data dikumpulkan melalui angket skala Likert yang mencakup aspek kepemimpinan digital, efektivitas pengelolaan, dan kesiapan digital anggota, kemudian dianalisis secara deskriptif menggunakan nilai rata-rata. Hasil penelitian menunjukkan bahwa kepemimpinan digital berada pada kategori tinggi dengan nilai rata-rata 3,80, sedangkan efektivitas pengelolaan MGMP berada pada kategori sangat tinggi dengan nilai rata-rata 4,00. Sementara itu, kesiapan digital anggota berada pada kategori sedang dengan nilai rata-rata 3,60, terutama pada aspek persepsi manfaat teknologi dalam meningkatkan kualitas kegiatan. Temuan penelitian menunjukkan bahwa pemanfaatan teknologi telah mendukung pengelolaan organisasi dan komunikasi kegiatan, namun belum sepenuhnya diikuti oleh penguatan visi digital dan peningkatan kesiapan digital anggota secara merata. Oleh karena itu, diperlukan penguatan visi digital organisasi, peningkatan kompetensi kepemimpinan berbasis teknologi, serta optimalisasi budaya digital untuk mendukung pengembangan profesionalisme guru secara berkelanjutan di era digital.